Medicinal Herbs and Biodiversity Resources in Nigeria: An Ethnographic Analysis of their Governance Mechanisms and Implications for Sustainable and Economic Development - Liadi, Olusegun Fariudeen; Lawal, Musediq; AKINRINDE, Olawale (Annals of Spiru Haret University. Economic Series, 2024)
This article examines the present systems for regulating biodiversity resource use, with a specific focus on Osun State, Nigeria. The study undertakes an exploratory research design due to the novelty of the subject matter. For data collection, qualitative research methodologies, specifically in-depth interviews (IDIs) and key informant interviews (KIIs), were purposefully adopted. Herbal medicine sellers were key participants in the in-depth interviews, while key informant interviewees included a diverse group of leaders of herb sellers’ associations, traditional healthcare providers, government officials responsible for Forestry Resources Management, practicing ethnobotanists, and knowledgeable academics with expertise relevant to the subject matter. The study further unfolds a comprehensive analysis of the threats to biodiversity, delving into the underlying causes and far-reaching consequences of biodiversity depletion in Nigeria. The study’s findings further shed a discerning light on the regulatory mechanisms governing biodiversity utilisation in Nigeria. Despite the existence of these mechanisms, they have struggled to realise the anticipated positive outcomes. This predicament is largely attributable to a lack of strong political will on the part of the government to ensure compliance among users of Nigeria’s rich biodiversity. A critical observation is that the legal and policy frameworks that oversee biodiversity in Nigeria have not undergone periodic reviews, rendering them out of touch with current societal dynamics. Consequently, traditional medicine practitioners and vendors of medicinal herbs, among other biodiversity users, have exploited this policy vacuum to exploit plant, tree, and other biodiversity resources unabated. Of notable concern is the unregulated exploitation of plants for medicinal purposes, particularly the trade in herbs, which has emerged as a significant threat to public health and well-being. This unchecked practice undermines the prospects of Sustainable Development Goal 3 (SDG-3), which prioritises health and well-being. In light of these findings, the study strongly advocates for a two-fold approach to address this pressing issue. First, it underscores the critical importance of fostering robust political will to enforce existing regulations and institute much-needed reforms. Secondly, constant monitoring and oversight of medicinal herb utilisation and other biodiversity resources in Nigeria by government agencies are deemed imperative to safeguard the nation’s natural wealth and the health of its citizens. Keywords: Biodiversity, Mechanisms, Medicinal Herbs, Ethnobotanist, SDGs JEL CLASSIFICATION: I30; I38; J18; J38; Q01